PINGGAWA-SAWI NELAYAN BUGIS-MAKASSAR DALAM ANALISIS RELASI INTERNAL DAN EKSTERNAL - Lampe, Munsi (P2KK LIPI, 2015)
This article aims to analyse the internal and external relations of Pinggawa-Sawi of Bugis-Makassar fishermen in South Sulawesi which has been persisted since hundred years ago.The shortcoming of ethnography study focusses on connection or coexistence between this traditional socio-economic organization of Bugis-Makassar fishermen and sea fishery modernization (with capitalism spirit) and global market makes the phenomena to be interesting to analyse/explain in the internal and external contexts.The study utilizes the data of Pinggawa-Sawi from the three Bugis-Makassar fishermen villages in South Sulawesi as material namely Sumpang Binangae (Barru), Lappa (Sinjai), and Tamalate (Takalar) which have long time ago respectively developed large scale type of light fishing (bagang rambo), long line tuna fishing (pancing tongkol), and purse seine (Gae). By applying the relational analysis found the four primary relational knots of Pinggawa-Sawi assure its survival in the wider communities and its mutual connection with sea fishery modernization, capitalism, and global market currents. By functioning the primary relational knots, the Pinggawa-Sawi has grown and rooted in the communities and coexisted with continually world economy development. Keywords: the survival of Pinggawa-Sawi, relational analysis, relational coreknots